STUDI PENDAHULUAN INTEGRASI KEISLAMAN PADA KOMPETENSI KESEHATAN MASYARAKAT - Susanti, Nofi; Indriani, Fatma (Inspiratif Pendidikan, 2023)
In Indonesia itself, there are various types of universities that are tied to religion, one of which is a public and private Islamic university to increase the religious integrity of each student (Umam 2018). The integration of Islam and science is endeavored to remain equal and to be in the same position in obtaining teachings and knowledge. The importance of Islamic integration in health is a strong reason for researchers to prove the extent of understanding of North Sumatra State Islamic University students in terms of integration and health. Purpose: This research was conducted to determine the extent of Islamic integration in competition in the field of public health. Methods: The design of this research is quantitative descriptive involving 35 students of the State Islamic University of North Sumatra who are in semester VII (seven). Samples were taken randomly which lasted for approximately 1 month (September-October). Results: UINSU FKM students are aware that skills in religious assessment are needed and also UINSU FKM students have awareness in data analysis and assessment skills, as well as related to policy development and program planning skills. in the last variable students have awareness related to leadership skills and system thinking, this proves that as students must have leadership skills and be able to solve problems broadly and dynamically in order to achieve the desired goals.